Uterine polyps pseudosarcomatous - Castillo, María (2015)
Pseudosarcomatous a case of recurrent endometrial polyps and uterine cervical mucosa in a postmenopausal woman is presented. Unlike were sarcoma botryoides type injuries or rhabdomyosarcoma by the absence of transverse striation and rhabdomyoblasts and lack of "subpitelial cambium" infiltration and epithelial neoplastic cells covered. We think that these injuries could represent what the epithelial dysplasia in the cervix. However, the low incidence with which they are presented can not be concluded by the mmento on its evolution and prognosis.